Exploring Civilization: Analyzing Siraj Munir’s Conception of Islamic Civilization - Masood, Farid bin; Arshad, Muhammad Rasheed (Journal of Islamic Thought and Civilization, 2023)
The current study provides the contextual background of the multifaceted and ever-evolving concept of civilization, tracing its origins and evolution in the field of social sciences along with its use in the Islamic context as well as its application in the pre-partition Indian subcontinent. The focus remains on the perspectives of Pakistani scholars regarding the notion of Islamic civilization with a specific emphasis on the ideas of Siraj Munir. The author classified the diverse perspectives of Pakistani scholars into three distinct categories namely materialists, fundamentalists, and idealists. Siraj Munir's views are situated within the idealist category. Through an in-depth analysis, the author provides a comprehensive examination of Munir’s ideas regarding the definition, formation, components, evolution, differences, and rise and fall of civilizations, as well as his articulation of Islamic and Pakistani civilizations. The current study offers a nuanced and critical understanding of the concept of civilization, providing valuable insights for scholars and researchers in the field.